The MAGPI Survey: radial trends in star formation across different cosmological simulations in comparison with observations at z ~ 0.3 - Mun, Marcie; Wisnioski, Emily; Harborne, Katherine E; Lagos, Claudia D P; Valenzuela, Lucas M; Remus, Rhea-Silvia; Mendel, J Trevor; Battisti, Andrew J; Ellison, Sara L; Foster, Caroline; Bravo, Matias; Brough, Sarah; et al. (Monthly notices of the Royal Astronomical Society, 2025)
We investigate the internal and external mechanisms that regulate and quench star formation (SF) in galaxies at $z \sim 0.3$ using MAGPI observations and the eagle, magneticum, and illustrisTNG cosmological simulations. Using simspin to generate mock observations of simulated galaxies, we match detection/resolution limits in star formation rates and stellar mass, along with MAGPI observational details including the average point spread function and pixel scale. While we find a good agreement in the slope of the global star-forming main sequence (SFMS) between MAGPI observations and all three simulations, the slope of the resolved SFMS does not agree within 1–2$σ$. Furthermore, in radial SF trends, good agreement between observations and simulations exists only for galaxies far below the SFMS, where we capture evidence for inside-out quenching. The simulations overall agree with each other between $\sim 1.5-4$$R_{\rm e}$ but show varying central suppression within $R \sim 1.5$$R_{\rm e}$ for galaxies on and below the SFMS, attributable to different AGN feedback prescriptions. All three simulations show similar dependencies of SF radial trends with environment. Central galaxies are subject to both internal and external mechanisms, showing increased SF suppression in the centre with increasing halo mass, indicating AGN feedback. Satellite galaxies display increasing suppression in the outskirts as halo mass increases, indicative of environmental processes. These results demonstrate the power of spatially resolved studies of galaxies; while global properties align, radial profiles reveal discrepancies between observations and simulations and their underlying physics.